From Tradition to Innovation: Conservative and Liberal Perspectives on Kemidi Rudat's Nonformal Learning - M Okta Dwi Sastra FM Marijo; Wadiyo Wadiyo; Suwardi Endraswara; Agus Cahyono; Girmaw Ashebir Sinshaw (AL-ISHLAH: Jurnal Pendidikan, 2025)
Kemidi Rudat, a traditional Sasak theater from Lombok, functions as a nonformal educational medium that transmits cultural, moral, and religious values through performance. While its aesthetic and historical aspects have been previously studied, limited research has examined its pedagogical role amidst sociocultural change, particularly the interplay of conservative and liberal educational values. This study employs a qualitative case study approach at the Panca Pesona Art Studio, using participatory observation, in-depth interviews, and documentation. Data were analyzed through the Miles and Huberman interactive model to explore how nonformal learning practices within Kemidi Rudat integrate preservation and innovation. Findings show that conservative values emphasize authenticity, such as traditional language, music, and etiquette, promoting cultural identity and character education. Liberal values, meanwhile, allow for innovation through story adaptation, use of modern instruments, and inclusivity, making the art form more appealing to younger generations. The Panca Pesona Studio mediates these values through a hybrid pedagogical model that balances tradition with creativity. Rather than conflicting, conservative and liberal perspectives function complementarily—conservatism anchors authenticity, while liberalism ensures relevance and sustainability. This dialectical learning model supports the preservation of cultural heritage while adapting to contemporary challenges. The study offers practical implications for educators, policymakers, and cultural practitioners in strengthening community-based arts education.